Imaging the Three-Dimensional Conductive Channel in Filamentary-Based Oxide Resistive Switching Memory - Celano, Umberto; Goux, Ludovic; Degraeve, Robin; Fantini, Andrea; Richard, Olivier; Bender, Hugo; Jurczak, Malgorzata; Vandervorst, Wilfried (Nano letters, 2015)
Filamentary-based oxide resistive memory is considered as a disruptive technology for nonvolatile data storage and reconfigurable logic. Currently accepted models explain the resistive switching in these devices through the presence/absence of a conductive filament (CF) that is described as a reversible nanosized valence-change in an oxide material. During device operation, the CF cycles billion of times at subnanosecond speed, using few tens of microamperes as operating current and thus determines the whole device’s performance. Despite its importance, the CF observation is hampered by the small filament size and its minimal compositional difference with the surrounding material. Here we show an experimental solution to this problem and provide the three-dimensional (3D) characterization of the CF in a scaled device. For this purpose we have recently developed a tomography technique which combines the high spatial resolution of scanning probe microscopy with subnanometer precision in material removal, leading to a true 3D-probing metrology concept. We locate and characterize in three-dimensions the nanometric volume of the conductive filament in state-of-the-art bipolar oxide-based devices. Our measurements demonstrate that the switching occurs through the formation of a single conductive filament. The filaments exhibit sizes below 10 nm and present a constriction near the oxygen-inert electrode. Finally, different atomic-size contacts are observed as a function of the programming current, providing evidence for the filament’s nature as a defects modulated quantum contact.